Properties of AA7075 aluminum alloy in aging and retrogression and reaging process - Ozer, Gokhan; Karaaslan, Ahmet (ELSEVIER SCIENCE BV, 2017)
A retrogression process was applied to AA7075 alloy at 180, 240 and 320 degrees C for 1, 30, 50, 70, 90 and 120 min. After the retrogression, aging treatment was reapplied with T6 conditions (120 degrees C, 24 h). The mechanical properties of aged samples were determined by V-Charpy and hardness tests and also, physical properties of samples were determined by electrical conductivity tests. Moreover, microstructural properties were characterized by light microscope and transmission electron microscope. The results show that the effects of the temperature and the duration of the retrogression and reagent on the impact toughness and hardness are related to the precipitates at the grain boundary.
Keywords: aluminum alloy; precipitate behavior, retrogression and reaging; impact toughness; hardness; electrical conductivity; ZN-MG ALLOY; EXFOLIATION CORROSION; AL; STRENGTH; MICROSTRUCTURE; PRECIPITATION; EVOLUTION; BEHAVIOR; MODEL; Metallurgy & Metallurgical Engineering